The Influence of Locus of Control and Student Competence on Students' Work Readiness - Dianastiti, Yelma; Putra, Rico Andhika; Yuswanto, Berlin's Liston (Universitas Negeri Padang, 2025)
Vocational education aims to produce a competent and competitive workforce, reduce unemployment, and strengthen the industrial sector. This study uses a quantitative method with multiple linear regression analysis to evaluate data from 122 students in grades X and XI. The results show that LOC (Locus of Control) and student competence significantly influence job readiness, with a combined contribution of 17.9%. Students with an internal LOC have high motivation and effective decision-making skills, which support their job readiness. Good student competence, including knowledge, skills, and attitude, strengthens their ability to adapt to the workplace. Although LOC's contribution to job readiness is only 8.8%, student competence shows a contribution of 16.1%. These findings highlight the importance of developing LOC and competence in vocational curricula to prepare students for a competitive job market. Educators should design programs that enhance students’ technical skills and LOC, equipping them to better face career challenges.